ANALISIS KLASIFIKASI PERBUATAN PIDANA DALAM UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Rustam (JURNAL SOSIO-KOMUNIKA, 2022)
One element of the economy is the existence of companies or corporations, which play a role in improving the economy of a country. Each of these companies will be engaged in a certain business field, which in the end the impact will be felt by the community. The impact as described above, sometimes is not only a positive impact, namely the welfare of the community or the country in general, but sometimes it is a negative impact that actually makes the state's economic situation in a downward direction. One of the negative impacts that make the economic situation in a destructive direction, one of which is due to money laundering. The type of research used is normative legal research. Normative legal research is research conducted by examining library materials (library research) or secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Currently in Indonesia, money laundering is regulated in Act Number 8 Year 2010 about Prevention and Eradication of Money Laundering, which replaces Act Number 15 Year of 2002 about the Crime of Money Laundering as amended by Act Number 25 Year 2003. In the latest provisions, the classification of acts or criminal acts as regulated in Act Number 8 Year 2010 above, can be divided into 2 (two) types of classification, namely Money Laundering Crimes and Crimes Related to Money Laundering. There are 4 (four) acts that are categorized as criminal acts related to money laundering, and 6 (six) crimes related to money laundering.